Dendritic cells pulsed with tumor cells killed by high hydrostatic pressure induce strong immune responses and display therapeutic effects both in murine TC-1 and TRAMP-C2 tumors when combined with docetaxel chemotherapy - Mikyšková, Romana; Štěpánek, Ivan; Indrová, Marie; Bieblová, Jana; Šímová, Jana; Truxová, Iva; Moserová, Irena; Fučíková, Jitka; Bartůňková, Jiřina; Špíšek, Radek; Reiniš, Milan (International journal of oncology, 2016)
High hydrostatic pressure (HHP) has been shown to induce immunogenic cell death of cancer cells, facilitating their uptake by dendritic cells (DC) and subsequent presentation of tumor antigens. In the present study, we demonstrated immunogenicity of the HHP-treated tumor cells in mice. HHP was able to induce immunogenic cell death of both TC-1 and TRAMP-C2 tumor cells, representing murine models for human papilloma virus-associated tumors and prostate cancer, respectively. HHP-treated cells induced stronger immune responses in mice immunized with these tumor cells, documented by higher spleen cell cytotoxicity and increased IFNγ production as compared to irradiated tumor cells, accompanied by suppression of tumor growth in vivo in the case of TC-1 tumors, but not TRAMP-C2 tumors. Furthermore, HHP-treated cells were used for DC-based vaccine antigen pulsing. DC co-cultured with HHP-treated tumor cells and matured by a TLR 9 agonist exhibited higher cell surface expression of maturation markers and production of IL-12 and other cytokines, as compared to the DC pulsed with irradiated tumor cells. Immunization with DC cell-based vaccines pulsed with HHP-treated tumor cells induced high immune responses, detected by increased spleen cell cytotoxicity and elevated IFNγ production. The DC-based vaccine pulsed with HHP-treated tumor cells combined with docetaxel chemotherapy significantly inhibited growth of both TC-1 and TRAMP-C2 tumors. Our results indicate that DC-based vaccines pulsed with HHP-inactivated tumor cells can be a suitable tool for chemoimmunotherapy, particularly with regard to the findings that poorly immunogenic TRAMP-C2 tumors were susceptible to this treatment modality.
Keywords: toll-like receptor 9; Interleukin-12; Immune System; docetaxel; Male; Cytotoxicity, Immunologic; protinádorové látky; slezina; Hydrostatic Pressure; Cell Line, Tumor; Interferon-gamma; infekce papilomavirem; Papillomavirus Infections; Taxoids; antigeny nádorové; Cancer Vaccines; Prostatic Neoplasms; interferon gama; Neoplasms, Experimental; mužské pohlaví; dendritické buňky; cytotoxicita imunologická; imunitní systém; Spleen; Toll-Like Receptor 9; Immunotherapy; Animals; lidé; experimentální nádory; taxoidy; Humans; zvířata; hydrostatický tlak; nádory prostaty; myši inbrední C57BL; Antigens, Neoplasm; imunoterapie; protinádorové vakcíny; myši; Mice, Inbred C57BL; nádorové buněčné linie; Dendritic Cells; Mice; interleukin-12; Docetaxel; Antineoplastic Agents